칫솔의 특허 경향 분석 - 최진성; 이영희; 조혜중; 김서진; 김혜은; 지형준; 안규현; 최홍란; 김옥준; Jin Sung Choi; Youmg Hee Lee; Hye Joung Cho; et al. (대한구강악안면병리학회지, 2016)
The basic instrument for oral hygiene is toothbrush. Many patents that are announced to enhance efficiency and convenience by changing shape and using new material. There are also patents regarding its various functions. This study, the purpose of study, was surveyed the toothbrush patents from 2005 to 2014. The patent search was done in site 'kipris' using keyword ‘toothbrush’. Among sorts of administrative measure, enrollment and extinction patents was searched, followed by classified patents into its shape, materials, function and electronic toothbrush. For the patents with function, detailed analysis was done. Total numbers of toothbrush patents decreased in 2006 to 2008, lowest in 2008, and steadily increased to 2014. The patents regarding shape was outnumbered material. Shape and material patents could be divided by handle portion and head portion patents, which patents of head portion is more than handle portion. The patents of function could be classified into certain situation or combinate functions to its natural function. Function patents increase with the ratio of total patents. For brush patents, they have a tendence of increase. In addition, from a shape and function, toothbrush patents going to be more variable. It choose small quantity batch production. From a shape of toothbrush, patents regarding head portion are going to increase. And it has a tendency to change the shape rather than the development of materials for efficiency of toothbrushing. Electronic toothbrush will be placed certain position, however, conventional toothbrush also will place large portion by estimating patent number and there be more progressive. Some patents will catch popularity like combination of brush and paste, replacement of brush head, attraction for toothbrushing, and hygiene tooth brush. Also disposable toothbrush and portable toothbrush are getting popularity along with social phenomenon.